PHARMACOGNOSTICAL AND PHYTOCHEMICAL SCREENING OF CORDIA ROTHII ROEM & SCHULT. - ZALA ARVINDBHAI HAJABHAI; DR. SAURABH S. PANDYA; DR. HARIBHAI A. RABARI (International Journal of Pharma and Bio Sciences, 2012)
Cordia rothii is a small tree growing mostly in tropical and temperate regions of India, Pakistan, Srilanka, North Africa and Arabica. Morphological and microscopical examination of Cordia rothii leaf was carried out using the reported methods in standard texts. Physical constants of crude drugs like loss on drying, ash values and extractive values were determined. Leaf constants like stomatal number, stomatal index, pallisade ratio, vein islet numbers and vein termination numbers were also determined to establish the standards. The preliminary phytochemical screening with the various qualitative chemical tests revealed the presence of carbohydrates, glycosides, saponins, steroids, triterpenes, proteins, amino acids and mucilage in the leaf extracts of Cordia rothii. The thin layer chromatography was also carried out as per the standard texts.